Microinvasive Oral Squamous Cell Carcinoma of Gingiva: An Enigma - Shakya, Prashamsa; Acharya, Poojan; Sharma, Shivalal; Shrestha, Ashish; Paunju, Nisha (Journal of Nepalese Society of Periodontology and Oral Implantology, 2021)
Microinvasive oral squamous cell carcinoma (MIOSCC) of gingiva is an early stage relatively ‘thin’ tumour without invasion of deep tissues. A 55-year old male reported with the chief complaint of gum swelling in lower right back jaw region for one month. On examination, diffuse, unscrappable, white homogenous plaque extending from 35 to 48 was present with a firm, sessile gingival growth approximately eight millimetre in diameter. A provisional diagnosis of verrucous leukoplakia was made. Hence, biopsy was performed which confirmed MIOSCC and mild dysplasia for different sites. The patient is on regular follow-up and with no signs of recurrence.